Coordination in vehicle routing : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Operations Research at Massey University, Palmerston North, New Zealand - Rivers, Catherine Margaret (Massey University, 2002)
Coordination involves the re-deployment of payload between depot and customer, and includes split deliveries, load transfers and load swapping, facilitated by the establishment of coordination sites at strategic locations. Real-world coordination includes mid-air refuelling, the use of temporary replenishment sites, trailers left for later uplift by their towing vehicles, bulk re-suppliers travelling to field operatives, fleet re-supply, and couriers swapping loads on the side of the road. This thesis models the coordination process and investigates the basic types of coordination in single depot, pure delivery systems in both the Euclidean plane and the rectilinear grid network. Strategies are developed for dealing with dynamic situations in the rectilinear grid, which are based on the pre-processing of scenarios in order that dispatchers may select a suitable response from an existing selection at the time that dynamic values are revealed. In addition, a procedure is suggested that reduces the number of edges and vertices of a rectilinear grid to those that may be useful within a coordination hull.
Keywords: Shipment of goods; Route choice; Plane geometry; Operations research; Fields of Research::350000 Commerce, Management, Tourism and Services::350400 Transportation